PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, DAN UKURAN DEWAN KOMISARIS TERHADAP INTENSITAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Putra, I Komang Septiadi; Ary Wirajaya, I Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The intensity of Corporate Social Responsibility (CSR) disclosure is a measure of communicating the company's contribution as a sense of responsibility for social and environmental impacts. The purpose of this study was to determine, analyze, and obtain empirical evidence about the effect of firm size, leverage, profitability, and board of commissioners size on the intensity of CSR disclosure. The number of samples in this study were 37 observations, which were selected using the purposive sampling method. Non-participant observation data collection method. The research design uses a quantitative approach in the form of associative aims to determine the relationship between two or more variables. The analysis technique used is Multiple Linear Regression Analysis. The results showed that the variable company size had a positive effect on the intensity of CSR disclosure, the leverage variable had a positive effect on the intensity of CSR disclosure, and the profitability variable had a positive effect on the intensity of CSR disclosure, while the size of the board of commissioners had no effect on the intensity of CSR disclosure. The results of this study can be used as a basis for management to increase the company's efforts in implementing the intensity of CSR disclosure